HUBUNGAN PENAMBAHAN BERAT BADAN IBU HAMIL DAN UKURAN LINGKAR LENGAN ATAS TERHADAP TAKSIRAN BERAT BADAN JANIN DI UPTD PUSKESMAS KEMALARAJA BATURAJA - Puspitasari, Yeviza (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
This study aimed to determine the relationship of maternal weight gain and the size of the upper arm circumference to birth weight estimated at UPTD Puskesmas Kemalaraja 2017 th . Methods, Used cross sectional analytic survey. The population in this study was all pregnant women in the third trimester of UPTD Puskesmas Kemalaraja 2017th . Gained as much as 35 pregnant women. The sampling technique using accidental sampling method. The instrumen in this study using a check list. Result, of the 35 respondens found the proportion of respondens who have a good weight gain most have normal fetal weight estimates taht as many as 85,7%, when the proportion of respondens who had less weight gain most have abnormal fetal weight estimates that as many as 14,3%. When seen from the result obtained Chi Square test p value = 0,002. The proportion of respondens who have a low risk of upper arm circumference most have normal fetal weight estimates that as many as 87,0%, when the proportion of respondens who have a high risk of upper arm circumference most have abnormal fetal weight estimates that as many as 13,0%. When seen from the result obtained Chi Square test p value = 0,000. Conclusion, There is a significant correlation between weight gain and estimated fetal weight and upper arm circumference and estimated fetal weight at UPTD Puskesmas Kemalaraja 2015 th.   Keywords : Weight gain, estimated fetal weight, and circumference of the upper arm.